The Mapping Elementary School Digital Transformation Readiness through SERI for Roadmap Development - Silalahi, Sondius Matogu Budiman; Santoso, Handri (Politeknik Ganesha Medan, 2026)
Digital transformation has become a strategic priority in elementary education as schools are increasingly expected to integrate digital technology into teaching, assessment, and institutional management. However, previous studies on school digital readiness have generally focused on isolated aspects such as infrastructure, digital literacy, or leadership, without providing an integrated assessment model that simultaneously evaluates process, technology, and organisational dimensions in elementary school contexts. This study aims to assess the digital transformation readiness of an elementary school using the Smart Education Readiness Index (SERI). A descriptive quantitative case-study approach was employed by adapting the SERI assessment matrix into the elementary school context. The assessment covered three dimensions process, technology, and organisation through twelve indicators. Data were collected through a structured assessment matrix, supporting document review, and expert validation involving two educational technology experts. The results indicate that the school reached a moderate level of digital transformation readiness. The strongest indicators were specific or specialised skills (2.635), digital infrastructure readiness (2.634), digital interconnectivity (2.598), and organisational planning indicators (2.562), while the weakest indicators were assessment (1.708), policy guidance (1.708), general or transversal skills (1.744), and digital storage (1.852). Unlike previous studies that mainly assess digital readiness through separate technological or pedagogical indicators, this study applies a multidimensional institutional assessment framework. This study contributes by proposing a structured and adaptable assessment approach for elementary school digital transformation that supports the development of a more measurable and context-sensitive digital transformation roadmap.